Schrödinger's Cat and Divine Action: Some Comments on the Use of Quantum Uncertainty to Allow for God's Action in the World - Brecha, Robert J. (Zygon, 2002)
I present results of recent work in the field of quantum optics and relate this work to discussions about the theory of quantum mechanics and God's divine action in the world. Experiments involving atomic decay, relevant to event uncertainty in quantum mechanics, as well as experiments aimed at elucidating the so–called Schrödinger’s–cat paradox, help clarify apparent ambiguities or paradoxes that I believe are at the heart of renewed attempts to locate God within our constructed physical theories and tend to narrow the gaps proposed as an opening for divine action. Some problems arise because of imprecise use of nonmathematical language to force quantum mechanics into an intuitive “classical” framework.